2017
DOI: 10.1074/jbc.m116.770032
|View full text |Cite
|
Sign up to set email alerts
|

Forkhead Box Protein 1 (FoxO1) Inhibits Accelerated β Cell Aging in Pancreas-specific SMAD7 Mutant Mice

Abstract: Edited by Jeffrey E. PessinThe mechanisms underlying the effects of exocrine dysfunction on the development of diabetes remain largely unknown. Here we show that pancreatic depletion of SMAD7 resulted in age-dependent increases in ␤ cell dysfunction with accelerated glucose intolerance, followed by overt diabetes. The accelerated ␤ cell dysfunction and loss of proliferation capacity, two features of ␤ cell aging, appeared to be non-cell-autonomous, secondary to the adjacent exocrine failure as a "bystander eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 45 publications
1
18
0
Order By: Relevance
“…Moreover, members of the FoxO subfamily shuttle from the cytoplasm to the nucleus and play an important role in cell proliferation, apoptosis, differentiation and oxidative stress resistance [35,36]. As the expression level and activity of FoxO1 are significantly increased in the liver tissues of patients with severe fatty liver disease and type 2 diabetes mellitus, FoxO1 has an important role in the occurrence and progression of human metabolic syndrome [37][38][39][40]. Moreover, FoxO1 is located at the intersection of many signal transduction pathways and may become a target for the treatment or intervention of many diseases [36,41,42].…”
Section: Akt Target Proteinsmentioning
confidence: 99%
“…Moreover, members of the FoxO subfamily shuttle from the cytoplasm to the nucleus and play an important role in cell proliferation, apoptosis, differentiation and oxidative stress resistance [35,36]. As the expression level and activity of FoxO1 are significantly increased in the liver tissues of patients with severe fatty liver disease and type 2 diabetes mellitus, FoxO1 has an important role in the occurrence and progression of human metabolic syndrome [37][38][39][40]. Moreover, FoxO1 is located at the intersection of many signal transduction pathways and may become a target for the treatment or intervention of many diseases [36,41,42].…”
Section: Akt Target Proteinsmentioning
confidence: 99%
“…In line with this concept, the β-cell–specific transcription factors Pdx1, NeuroD1, Nkx6.1, and MafA seem to be required for β-cells to be fully functional, whereas their loss correlates with β-cell dysfunction and β-cell loss (2325). As such, we performed PDL on MIP-GFP mice, and sorted β-cells via FACS at serial time points after PDL to asses Pdx1, NeuroD1, Nkx6.1, and MafA mRNA levels in β-cells by quantitative RT-PCR and Western blotting.…”
Section: Resultsmentioning
confidence: 69%
“…FoxO1 is a transcription factor that plays a key protective role against β-cell failure during stress (2325). Previous reports have shown that FoxO1 and Stat3 antagonize each other in the regulation of T-cell function (34,35) and leptin signaling transduction (36,37).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations